Tactile acuity testing at the neck: A comparison of methods. (December 2017) - Harvie, Daniel S.; Kelly, Joan; Buckman, Hayden; Chan, Jonathan; Sutherland, Grace; Catley, Mark; Novak, James; Tuttle, Neil; Sterling, Michele
Abstract: Background: Interest in measurement of tactile acuity in musculoskeletal practice has emerged following its link to functional reorganization of the somatosensory cortex in ongoing pain states. Several tactile acuity measurement methods have been described but have not been thoroughly investigated in the cervical region. Objective: This study examined reliability, concurrent validity and responsiveness of four tests of tactile acuity—Two-point discrimination, Point-to-point, Graphesthesia, and Localisation tests—at the cervical region. Method: Forty-two healthy participants were included. In Part 1 (n = 22), participants' tactile acuity was assessed at two time points, 30 min apart, to determine the test-retest reliability and concurrent validity of each of the tests. In Part 2 (n = 20), participants received five daily tactile training sessions, delivered via a vibro-tactile device. Tactile acuity was assessed pre- and post-training to examine responsiveness of each test. Results: Two-point discrimination demonstrated excellent test-retest reliability (ICC = 0.85, SEM = 3.7 mm), Point-to-point and Localisation tests demonstrated good reliability (ICC = 0.60, SEM = 2.8 mm; ICC = 0.60, SEM = 8.8%), and Graphesthesia demonstrated fair reliability (ICC = 0.48, SEM = 1.9/20). There was no significant correlation among measures. Only Graphesthesia failed to show responsiveness to change following training. Conclusion: The reliability of Two-point discrimination appears superior to other examined tests of tactile acuity, however measurement variability should be considered. Two-point discrimination, Point-to-point, and Localisation tests appear responsive to change, although testing in clinical samples is needed. The lack of concurrent validity among tests suggests that they cannot be used interchangeably. Highlights: Two-point discrimination was the most reliable test of tactile acuity examined. All examined tests appear responsive to change. Tactile acuity tests cannot be used interchangeably and may test unique aspects. Examination in clinical samples is needed.